Grumpy monkey : mom for a day - Lang, Suzanne; Lang, Max, 1982- (New York : Random House Studio, 2025)
"Grumpy Monkey offers to babysit the little animals in the jungle, but when things go haywire, help comes from an unexpected source."--
Added content may vary.
Ages 4-8.
Keywords: Chimpanzees -- Juvenile fiction; Babysitters -- Juvenile fiction; Babysitters and babysitting -- Fiction; Jungle animals -- Juvenile fiction; Animal fiction; Picture books